Effect of intramedullary pin size on reducing bone plate strain - Hulse, D.; Ferry, K.; Fawcett, A.; Gentry, D.; Hyman, W.; Geller, S.; Slater, M. (Veterinary and Comparative Orthopaedics and Traumatology, 2000)
The degrees of plate strain, coupled with various diameters of intramedullary pins, is reported. In addition, the fatigue life and stiffness of the plate/pin construct was determined.
Keywords: Plate strain; intramedullary pins